Implementation of the Make a Match Learning Model in Pancasila and Citizenship Education in Elementary Schools - Lubis, Maulana Arafat; Samsuddin, Samsuddin; Anzelina, Dewi; Azizan, Nashran; Siregar, Hanifah Khairiyah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan IAIN Manado, 2024)
The learning system in Indonesia requires appropriate changes in advancing education, especially in elementary schools. If the learning process is carried out very well, it will also get very good grades by choosing the right learning models. The learning model is a design pattern that aims to achieve learning according to the basic competencies that have been determined from student learning outcomes. The relationship between the urgency of the Make a Match learning model applied to PPKn (Pancasila and Civic Education) learning in elementary schools, namely, it can increase student active participation, build a strong understanding of concepts, improve social skills, make learning more interesting, and encourage deep understanding. Overall, the urgency of implementing the Make a Match learning model in PPKn learning in elementary schools is to ensure that students not only memorize Pancasila values, but also understand, internalize, and apply them in everyday life through active, interactive, and enjoyable learning experiences. The purpose of the study was to improve students' PPKn learning outcomes through the application of the Make a Match learning model. The subjects of the study were 20 students of MIN 3 Padangsidimpuan. This research uses a classroom action research method by referring to Kurt Lewin's theory which has four stages, namely: planning, action, observation, and reflection. Data collection uses tests and observations. Data are analyzed descriptively using quantitative and qualitative approaches. The quantitative approach is from test data, while the qualitative approach is from observation data. The results of the study prove that students experienced an increase in their learning with an average score of 85% in cycle II meeting II.